Combination of Cytokine-Induced Killer Cells and Programmed Cell Death-1 Blockade Works Synergistically to Enhance Therapeutic Efficacy in Metastatic Renal Cell Carcinoma and Non-Small Cell Lung Cancer - Wang, Zibing; Liu, Xiaoli; Till, Brian; Sun, Miaomiao; Li, Xiang; Gao, Quanli (Frontiers in Immunology, 2018)
Introduction: Programmed cell death-1 (PD-1) inhibition therapy has changed the treatment paradigm of metastatic renal cell carcinoma (MRCC) and non-small cell lung cancer (NSCLC). However, attempts to use the drug as a single agent have achieved only limited clinical success. To further enhance the clinical benefits of monotherapy, combination therapies will likely be necessary. Cytokine-induced killer (CIK) cells are a heterogeneous subset of ex-vivo expanded T lymphocytes that have been shown to prolong the survival of cancer patients. We are conducting a study to evaluate the efficacy of PD-1 inhibitor in combination with CIK cells in relapsed/refractory MRCC and NSCLC, and to analyze potential biomarkers to predict which patients will benefit most from the combined therapy. Case presentation: The results of two patients treated in an ongoing clinical trial for MRCC and NSCLC are described here. The tumor cells from patient 1 strongly expressed PD-L1, and there was extensive tumor infiltration by CD3+ T cells; however, no PD-1 staining was seen. The tumor biopsy from Patient 2 exhibited moderate CD3+ T cell infiltration, but no PD-1 or PD-L1 expression. nsSNVs, along with higher indel mutations, in patient 1 and nsSNVs along with higher tumor mutation burden in patient 2 correlate with tumor-infiltrating CD3+ lymphocyte density. Patient 1 achieved a complete response, and Patient 2 achieved a near-complete response. Conclusion: A PD-1 inhibitor in combination with CIK cells led to potent anti-tumor activity in MRCC and NSCLC; CD3+ T cell infiltration in baseline tumor biopsies is a potential predictive biomarker. This approach is being further investigated in an ongoing phase I trial.